Smart Tourism-based Urban Tourism Governance in Bali as a Form of Integration of Digital Innovation and Local Community Participation - I Putu Eka Pradipta; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study examines the governance of urban tourism based on smart tourism in Bali as an integration of digital innovation and local community participation. The development of urban tourism in Denpasar and the Sarbagita metropolitan area has increased destination complexity due to the significant growth of tourist arrivals during 2023–2025. This condition requires an adaptive, efficient, and sustainable governance model through the application of digital technology. This research employs a qualitative approach with a case study design, using in-depth interviews, field observation, and documentation analysis of tourism regulations and digital transformation policies. The findings reveal that smart tourism implementation in Bali has begun through the digitalization of destination information services and tourism promotion platforms in line with Presidential Regulation No. 95 of 2018 on Electronic-Based Government Systems. However, smart tourism practices remain partial, characterized by private sector dominance in the digital tourism ecosystem and limited cross-agency data integration. Local community participation is still largely operational rather than strategic in smart destination policy planning, potentially leading to unequal distribution of digital tourism benefits. The study highlights that the success of smart tourism in Bali requires strengthening collaborative governance involving government, private stakeholders, traditional village institutions, and local communities to ensure that digital transformation aligns with Bali’s cultural tourism principles based on Tri Hita Karana. Inclusive and participatory smart tourism has the potential to support high-quality and sustainable urban tourism development in Bali. Keywords: Bali, Community Participation, Destination Governance, Digital Innovation, Smart Tourism, Urban Tourism.